KONSELING REALITA BERBASIS NILAI-NILAI Q. S. AR RA’D: 11 UNTUK MENGURANGI PERILAKU BULLYING PADA SISWA SMP - Nur Azizah; Bakhrudin All Habsy; Elisabeth Christiana; Denok Setiawati (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2024)
Bullying is an act of using power to hurt a person or group of people verbally, physically or psychologically so that the victim feels depressed, traumatized and helpless. The aim of this research is to decrease the rate of decline in bullying behavior in junior high school students and turn their negative behavior into positive behavior according to the values of Q. S. Ar Ra'd verse 11 for bullying perpetrators. This research method uses experimental research in the form of Single Subject Research (SSR). The results of this research show a decrease in bullying scores from score of 108 to score of 45 with positive behavioral changes in accordance with the rules set out in the Al-Qur'an.